Application Of Audit In Management Of Financial Reports Based On SAK Syariah - Adriani; Jamaluddin Madjid; Amiruddin K (Sekolah Tinggi Ilmu Ekonomi LPI Makasar, 2025)
This study uses a qualitative research method. By using a literature review, a systematic approach to collecting, evaluating, and synthesizing relevant literature in a particular field of research. Experts recognize the importance of a literature review as an initial step in the research process that allows researchers to understand the research context, review previous findings, and identify knowledge gaps that still need to be explored. The Results of this Study The Implementation of Sharia Audits in Financial Institutions has been carried out by prioritizing sharia values and laws to carry out financial statement audits based on Sharia SAK. Parties that play a role in supervising Sharia Financial Institutions, Bank Indonesia, National Sharia Council (DSN), Sharia Supervisory Board (DPS). In carrying out their functions, BI and DSN play a greater role in supervision while DPS plays a greater role in controlling Islamic banks.